Diagnostic value of impulse oscillometry in chronic obstructive pulmonary disease: a multicentre, retrospective, observational study - Hui Zhou; Hao Wang; Lin Liu; Lei Chen; Tao Wang; Yongchun Shen; Lijuan Gao; Dan Xu; Fu-Qiang Wen; Yanqiu Wu; Shuguang Xiong; Rong Qiu; et al. (BMJ Open)
Objectives Diagnosis and assessment of chronic obstructive pulmonary disease (COPD) rely extensively on spirometry, which necessitates patient cooperation. The clinical value of impulse oscillometry (IOS) as a non-volitional method in patients with COPD remains uncertain.Design This retrospective observational study was conducted using patient data from between January 2014 and December 2015.Setting Five public hospitals in China: West China Hospital, Nuclear Industry 416 Hospital, Suining Central Hospital, Affiliated Hospital, Medical College of Chengdu University and 363 Hospital.Participants The study included 6307 participants aged>40 years, comprising 2109 COPD patients and 4198 general non-COPD individuals, according to the Global Initiative for Obstructive Lung Disease (GOLD) spirometry standard. Participants with lung cancer, pulmonary tuberculosis, pneumonia or those who underwent lung resection were excluded from the study.Outcome measures and analysis Demographic data, spirometry results and IOS results were collected. Spearman’s correlation analysis was used to examine the correlation between the IOS and spirometry parameters. Receiver operating characteristic curve analysis was used to evaluate the IOS performance in COPD diagnosis and severity staging.Results Patients with COPD exhibited significant increases in Z5, R5, R20, R5−R20, Fres and Rp, but a decrease in X5 compared with non-COPD subjects (p<0.0001). IOS parameters, including Z5, R5−R20, Fres, Rp and X5, varied with the GOLD stages, with mild-to-moderate correlations with MMEF25%–75%, forced expiratory volume in one second (FEV1)/forced vital capacity and FEV1%, respectively. However, the combination of these five IOS parameters did not exhibit ideal performance in diagnosing COPD (area under the curve (AUC) 0.78; sensitivity 63.68%; specificity 80.09%), differentiating GOLD stage 1 patients from the general non-COPD population (AUC 0.71; sensitivity 54.71%; specificity 77.49%) or identifying GOLD stages 3 and 4 patients among those with COPD (AUC 0.75; sensitivity 69.51%; specificity 70.32%).Conclusion IOS parameters, while showing good correlation with spirometry in patients with COPD, did not perfectly substitute for spirometry in diagnosing COPD, especially in the early and advanced stages of the disease.